The Periodicity of Square Fuzzy Neutrosophic Soft MatricesBased on Minimal Strong Components - Rameshware K; Kavitha M; Murugadass P (Neutrosophic Sets and Systems)
Abstract. In this paper Minimal Strong Component (MSC) of a Fuzzy Neutrosophic Soft Matrix (FN SM) is suggested. By employing the connection of periodicity behaviours of FN SM with its cut matrices, the periodicity of power sequence of FN SM is described. Especially the concepts of MSC is given and the periodicity of a FN SM by its (Theorem-4.10) on the basis of the above results, the greatest value max ∑ li=n = [li] of the periodicity of all SFN SM for a given positive integer n is obtained. So in a case we have clearly resolved the problem of the greatest value of all periodicity FN SM for a given positive integer n.